Question
upstudy study bank question image url

Solve the following inequality and graph the solution. Answer using interval \( x^{2}+2 x-3 \geq 0 \)

Ask by Mckenzie Chan. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution to the inequality \( x^{2} + 2x - 3 \geq 0 \) is \( x \leq -3 \) or \( x \geq 1 \). In interval notation, this is written as \( (-\infty, -3] \cup [1, \infty) \).

Solution

We start with the inequality   x² + 2x – 3 ≥ 0. Step 1. Factor the quadratic:   x² + 2x – 3 = (x – 1)(x + 3). Step 2. Find the zeros by setting each factor equal to 0:   x – 1 = 0 ⟹ x = 1,   x + 3 = 0 ⟹ x = –3. Step 3. Determine the sign in the intervals created by the zeros:  • For x < –3 (e.g., x = –4):   (x – 1) is negative and (x + 3) is also negative, so their product is positive.  • For –3 < x < 1 (e.g., x = 0):   (x – 1) is negative and (x + 3) is positive, so their product is negative.  • For x > 1 (e.g., x = 2):   Both (x – 1) and (x + 3) are positive, so their product is positive. Since we need (x – 1)(x + 3) to be greater than or equal to 0, we include the intervals where the expression is positive or zero. Note that at x = –3 and x = 1 the expression equals 0. Step 4. Write the solution in interval notation:   (–∞, –3] ∪ [1, ∞). Graph of the solution:  Number line representation:   <------●===========○-----------●========>    –∞ –3 (no solution) 1 ∞ Here, ● at –3 and 1 indicates that these endpoints are included (closed circles), and the shaded regions extend to negative infinity before –3 and positive infinity after 1. Final Answer in Interval Notation:   (–∞, –3] ∪ [1, ∞).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the inequality \( x^{2} + 2x - 3 \geq 0 \), we first find the roots of the corresponding equation \( x^{2} + 2x - 3 = 0 \) using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Here, \( a = 1 \), \( b = 2 \), and \( c = -3 \). Plugging in these values, we calculate: \[ x = \frac{-2 \pm \sqrt{2^2 - 4(1)(-3)}}{2(1)} = \frac{-2 \pm \sqrt{4 + 12}}{2} = \frac{-2 \pm \sqrt{16}}{2} = \frac{-2 \pm 4}{2} \] This gives us the roots \( x = 1 \) and \( x = -3 \). Next, we analyze the sign of the quadratic expression in the intervals determined by the roots: \( (-\infty, -3) \), \( (-3, 1) \), and \( (1, \infty) \). 1. In the interval \( (-\infty, -3) \), choose \( x = -4 \): \( (-4)^2 + 2(-4) - 3 = 16 - 8 - 3 = 5 \) which is positive. 2. In the interval \( (-3, 1) \), choose \( x = 0 \): \( 0^2 + 2(0) - 3 = -3 \) which is negative. 3. In the interval \( (1, \infty) \), choose \( x = 2 \): \( 2^2 + 2(2) - 3 = 4 + 4 - 3 = 5 \) which is positive. Now, putting this together, the solution to the inequality \( x^{2} + 2x - 3 \geq 0 \) means we include the intervals where the expression is positive or zero. Therefore, the solution is: \[ (-\infty, -3] \cup [1, \infty) \] For graphing, plot the points \( -3 \) and \( 1 \) on a number line. Shade the regions to the left of \( -3 \) (including \( -3 \)) and to the right of \( 1 \) (including \( 1 \)) to demonstrate the solution visually. Final answer in interval notation: \[ (-\infty, -3] \cup [1, \infty) \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy